GAMBARAN STATUS GIZI MENGGUNAKAN KMS REMAJA PADA SANTRI PUTRI DI SMA UNGGULAN HAF-SA ZAINUL HASAN BPPT GENGGONG KABUPATEN PROBOLINGGO - Meiriyantika, Maulida Khofifah; Mansur, Herawati; Rosmalawati, Ni Wayan Dwi (Universitas Muhammadiyah Mataram, 2024)
Abstract: The health status of adolescents is an important thing that must be considered. The teenage period is one of the stages of a person's life where weight and height growth peaks. This research aims to determine the description of nutritional status using KMS for young women at the leading high school Haf-Sa Zainul Hasan BPPT Genggong. This study aims to determine the description of nutritional status using KMS adolescents for female students at Unggulan Haf-Sa Zainul Hasan BPPT Genggong High School. The design in this research is descriptive quantitative. The population in this study were female students of Class XI and XII SMA Unggulan Haf-Sa Zainul Hasan BPPT Genggong, totaling 104 students. The sample was taken using proportional random sampling technique, totaling 51 respondents. The data collection tool measures nutritional status through weight and height which is plotted on the KMS chart for adolescents. Data analysis used descriptive analysis. The results of this study showed that most (54.90%) had more nutritional status and almost half (45.10%) had good nutritional status. Based on the results of research on the nutritional status of female students, the more dominant nutritional status. It is hoped that schools and health centers will hold socialization regarding general guidelines recommends consuming food according to